Impact of remote monitoring on clinical outcomes for patients with heart failure and atrial fibrillation: results from the REM‐HF trial. (7th January 2020) - Zakeri, Rosita; Morgan, John M.; Phillips, Patrick; Kitt, Sue; Ng, G. Andre; McComb, Janet M.; Williams, Simon; Wright, David J.; Gill, Jaswinder S.; Seed, Alison; Witte, Klaus K.; Cowie, Martin R.; et al.
Abstract: Aims: Studies of remote monitoring (RM) in heart failure (HF) speculate that patients with atrial fibrillation (AF) derive the greatest benefit. We compared the impact of RM vs. usual care on clinical outcomes for patients with and without AF enrolled in the Remote Management of Heart Failure Using Implanted Electronic Devices (REM‐HF) trial. Methods and results: Rhythm status was available for 1561 patients (94.6%). Three categories were defined based on total AF duration during the first year of follow‐up: (i) no AF ( n = 1211, 77.6%), (ii) paroxysmal AF (≥6 min to ≤7 days; n = 92, 5.9%), and (iii) persistent/permanent AF (>7 days; n = 258, 16.5%). Clinical activity, mortality, and hospitalisation rates were compared between treatment strategies for each group. RM resulted in a greater volume of clinical activity in patients with any AF, vs. no AF, with the highest per‐patient intervention required for patients with persistent/permanent AF. During 2.8 ± 0.8 years of follow‐up, RM was not associated with a reduction in all‐cause or cardiovascular mortality for patients with AF. However, in patients with persistent/permanent AF, RM conferred an increased risk of recurrent cardiovascular [hazard ratio (HR) 1.40, 95% confidence interval (CI) 1.06–1.85, P = 0.018] and HF‐related (HR 2.05, 95% CI 1.14–3.69, P = 0.016) hospitalisations. Conclusion: In patients with HF and a cardiac implanted electronic device, RM generated greater clinical activity for patients with AF, with no associated reduction in mortality, and conversely, greater risk of cardiovascular hospitalisation amongst patients with persistent/permanent AF. RM strategies may vary in their capability to guide HF management; modified approaches may be needed to improve outcomes for HF patients with AF.